El «enfoque de las capacidades» de Martha Nussbaum frente el problema de la ética animal - Martínez Becerra, Pablo (Veritas, 2015)
This paper describes the capabilities approach Martha Nussbaum as an attempt to justify the inclusion of non-human animals within the civic rights dimension is studied. In this perspective is to establish certain «direct duties of justice» for sentient beings, possessors of some complexity, that the State must seek precautionary and as a minimum requirement. After analyzing this proposal, they develop some of the criticism caused by the «animal ethics» defended by Nussbaum, among which are counted Donaldson, Kymlicka, Smith, Cortina and Schlosberg. (English)